2019
DOI: 10.1055/s-0039-1690158
|View full text |Cite
|
Sign up to set email alerts
|

β-Selective One-Pot Synthesis of Acyl-C-Glycosides via Corey–Seebach Umpolung Reaction

Abstract: C-Glycosides are commonly used as carbohydrate mimics in drug development due to their stability against enzymatic and chemical hydrolysis. In this Synpacts article we elaborate on our fast and efficient β-selective approach towards protected and unprotected acyl glycosides. Application of a Corey–Seebach umpolung reaction enables the exclusive formation of the β-anomer of aromatic acyl-C-glycosides in good to excellent yields.1 Introduction2 C-Glycosylation of Benzylated Glycosyl Donors3 C-Glycosylation of Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…This temperature was necessary to avoid the competing E2-elimination occuring when employing, for example, d-glucose donors. [28,29] Running the reaction at 0 °C gave Cacyl α-d-mannopyranoside 22α as the only C-glycosylation product in 11 % overall yield with poor reproducibility. In contrast to the previously reported β-selective method, the products of the Cu-catalyzed reactions are exclusively αconfigured (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This temperature was necessary to avoid the competing E2-elimination occuring when employing, for example, d-glucose donors. [28,29] Running the reaction at 0 °C gave Cacyl α-d-mannopyranoside 22α as the only C-glycosylation product in 11 % overall yield with poor reproducibility. In contrast to the previously reported β-selective method, the products of the Cu-catalyzed reactions are exclusively αconfigured (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies revealed that in the attempted one‐pot C ‐glycosylation of d ‐mannopyranose 9 , l ‐rhamnopyranose 10 or d ‐lyxopyranose 11 derivatives the formation of the iodide donors 15α ‐ 17α was successful, but nucleophilic attack of the lithiated dithiane 19 a was inhibited at the reaction temperature (‐95 °C to 0 °C). This temperature was necessary to avoid the competing E2‐elimination occuring when employing, for example, d ‐glucose donors [28,29] . Running the reaction at 0 °C gave C ‐acyl α‐ d ‐ mannopyranoside 22α as the only C ‐glycosylation product in 11 % overall yield with poor reproducibility.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations